A Synoptic‐Scale Wavelike Structure in the Nighttime Equatorial Ionization Anomaly. Issue 2 (17th February 2021) - Rodríguez‐Zuluaga, J.; Stolle, C.; Yamazaki, Y.; Xiong, C.; England, S. L.
Abstract: Both ground‐ and satellite‐based airglow imaging have significantly contributed to understanding the low‐latitude ionosphere, especially the morphology and dynamics of the equatorial ionization anomaly (EIA). The NASA Global‐scale Observations of the Limb and Disk (GOLD) mission focuses on far‐ultraviolet airglow images from a geostationary orbit at 47.5°W. This region is of particular interest at low magnetic latitudes because of the high magnetic declination (i.e., about ‐20°) and proximity of the South Atlantic magnetic anomaly. In this study, we characterize an exciting feature of the nighttime EIA using GOLD observations from October 5, 2018 to June 30, 2020. It consists of a wavelike structure of a few thousand kilometers seen as poleward and equatorward displacements of the EIA‐crests. Initial analyses show that the synoptic‐scale structure is symmetric about the dip equator and appears nearly stationary with time over the night. In quasi‐dipole coordinates, maxima poleward displacements of the EIA‐crests are seen at about ± 12° latitude and around 20 and 60° longitude (i.e., in geographic longitude at the dip equator, about 53°W and 14°W). The wavelike structure presents typical zonal wavelengths of about 6.7 × 10 3 km and 3.3 × 10 3 km. The structure's occurrence and wavelength are highly variable on a day‐to‐day basis with no apparent dependence on geomagnetic activity. In addition, a cluster or quasi‐periodic wave train of equatorial plasma depletions (EPDs) is often detected within the synoptic‐scale structure. We further outline the difference in observing these EPDs from FUV images and in situ measurements during a GOLD and Swarm mission conjunction. Key Points: Characteristics of a wavelike structure in the nighttime equatorial ionization anomaly are reported using GOLD far‐ultraviolet observations The structure is symmetric about the dip equator, appears stationary with time over the night, and is highly variable on a day‐to‐day basis A cluster or quasi‐periodic wave train of equatorial plasma depletions is often detected within the synoptic structure